Stress Management and Resiliency Training for Healthcare Professionals: A Mixed-Methods, Quality-Improvement, Cohort Study. Issue 1 (January 2021) - Dossett, Michelle L.; Needles, Emma W.; Nittoli, Caroline E.; Mehta, Darshan H.
Abstract : Objective: To assess the effects of a multi-modal resilience program, the Stress Management and Resiliency Training (SMART) Program, on healthcare professional well-being and job satisfaction. Methods: This pilot, mixed-methods, quality improvement, cohort study assessed perceived stress, physical and mental health, job satisfaction, burnout, and value of the curriculum to attendees. Results: Participants experienced a significant reduction in perceived stress ( P  < 0.001) and significant improvements in global mental health ( P  = 0.001), physical health ( P  = 0.045), and job satisfaction ( P  = 0.047). There was no significant improvement in burnout. Qualitative analysis of free text responses revealed appreciation for the skills taught, increased resiliency, and a positive impact on relationships. Conclusions: Delivering the SMART Program to healthcare professionals is feasible and may serve as a useful tool for reducing stress and increasing resilience. Abstract : Supplemental Digital Content is available in the text